2018
DOI: 10.1111/deve.12159
|View full text |Cite
|
Sign up to set email alerts
|

Does Microfinance Reduce Poverty among the Poorest? A Macro Quantile Regression Approach

Abstract: The goal of this paper is to provide empirical evidence to determine whether microfinance, measured through a country's gross loan portfolio per capita, has a heterogeneous effect on poverty reduction among countries with different levels of poverty. We have used a panel‐data quantile regression with a data set for 57 countries for the years 2005, 2008, and 2011 to estimate the distributional impacts of microcredits on two poverty indices. Results reveal not only that microfinance significantly reduces the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
(53 reference statements)
2
16
1
Order By: Relevance
“…Also, the elite capture mechanism is widely distributed over the rural credit market in China, leading to potential structure distortions, function dislocation, and target deviation. This conclusion is different from that of Khandker [29] and Lacalle-Calderon et al [31], who found that microfinance benefits those in extreme poverty more than those in moderate poverty, suggesting that microcredit reaches and benefits even the poorest individuals. Farmers at the lowest income level may be unable to fulfill their basic production and living consumption demand.…”
Section: Analysis Of Empirical Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…Also, the elite capture mechanism is widely distributed over the rural credit market in China, leading to potential structure distortions, function dislocation, and target deviation. This conclusion is different from that of Khandker [29] and Lacalle-Calderon et al [31], who found that microfinance benefits those in extreme poverty more than those in moderate poverty, suggesting that microcredit reaches and benefits even the poorest individuals. Farmers at the lowest income level may be unable to fulfill their basic production and living consumption demand.…”
Section: Analysis Of Empirical Resultscontrasting
confidence: 64%
“…Beaman et al [28] employed a two-stage loan and grant experiment and found that returns to capital were higher for farmers who borrowed than those who did not. Lacalle-Calderon et al [29] found not only that microfinance significantly reduced the incidence and depth of poverty, but also that this effect differed across different poverty levels (quantiles).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… See e.g. Bergh and Nilsson (2014); Fosu (2018); Gnangnon (2019); Lacalle‐Calderon, Perez‐Trujillo, and Neira (2018); Le Goff and Singh (2014); Kiendrebeogo and Minea (2016); Kpodar and Singh, (2011); Santos‐Paulino (2017); Singh and Huang (2015); and Sotomayor (2021). …”
mentioning
confidence: 99%